2008
DOI: 10.1007/s10545-008-1033-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic programming: Role of nutrition in the immediate postnatal life

Abstract: Although genes and dietary habits are generally implicated in the aetiology of the prevailing obesity epidemic, the steep increase in the incidence of obesity within a relatively short span of time suggests that other contributing factors may be at play. The role of nutritional experience during the very early periods of life is increasingly being recognized as contributing to growth and metabolic changes in later life. Epidemiological data and studies from animal models have established a strong correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 68 publications
1
52
0
1
Order By: Relevance
“…[15] Aslında obezite ve etiyolojisi, yeme bağımlılığı tanımının ötesinde genetik, davranışsal ve çevresel faktörlerin bir arada etkili olduğu bir durum olarak tanımlamak şimdilik daha doğru görünmektedir. [16] …”
Section: Tanımı Ile İlişkili Görüşlerunclassified
“…[15] Aslında obezite ve etiyolojisi, yeme bağımlılığı tanımının ötesinde genetik, davranışsal ve çevresel faktörlerin bir arada etkili olduğu bir durum olarak tanımlamak şimdilik daha doğru görünmektedir. [16] …”
Section: Tanımı Ile İlişkili Görüşlerunclassified
“…We have recently shown that blocking leptin action using a leptin antagonist predisposed newborn rats to body weight gain and leptin resistance at adulthood (Attig et al 2008). Consequently, all events that affect leptin action during this developmental period such as inappropriate diet of dams during pregnancy (high caloric diet or energy restriction) impair hypothalamic neuronal projections and promote later in life metabolic and endocrine disorders (Kirk et al 2009, Patel et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in the hypothalamic circuitry controlling feeding behavior and body weight management during this critical period of development are involved (11,13,23,38,45,50). Surprisingly, the sedentary female rats from the small litters (group SS) did not show body weight significantly different from that of the controls (group CS) at the age of 120 days.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional experiences at early life lead to the changes of growth and metabolism in later stages. The research demonstrates that the development of adipose cellularity at this early stage can determine the body composition of the adult and thus the appearance and aggravation of obesity-related diseases (6,14,23,35,37,38,42,45).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation